Hall Effect on the Doped Semiconductor Superlattice with an In-plane Magnetic Field Under Influence of an Intense Electromagnetic Wave - Bau, Nguyen Quang; Hoi, Bui Dinh; Phong, Tran Cong (Communications in Physics, 2014)
The Hall effect is studied theoretically in a doped semiconductor superlattice (DSSL) subjected to a crossed dc electric field and magnetic field in the presence of an intense electromagnetic wave (EMW). By using the quantum kinetic equation for electrons interacting with acoustic phonons at low temperature, we obtain expressions for the magnetoresistance as well as the Hall coefficient in dependence on the external fields and characteristic parameters of the DSSL. Analytical results are numerically evaluated for the GaAs:Si/GaAs:Be DSSL. The dependence of the magnetoresistance on the magnetic field is consistent with the result obtained for some two-dimensional electron systems. The Hall coefficient depends weakly on the magnetic field and its value in the presence of the EMW is smaller than that of the case without EMW.